Broadband internet and new firm location decisions in rural areas - Kim, Younjun; Orazem, Peter F. (American Journal of Agricultural Economics, 2017)
Keywords: dept.eco; peer-reviewed

Does Agglomeration Matter Everywhere?: New Firm Location Decisions in Rural and Urban Markets - Artz, Georgeanne M.; Kim, Younjun; Orazem, Peter F. (Journal of Regional Science, 2016)
We test whether commonly used measures of agglomeration economies encourage new firm entry in both urban and rural markets. Using new firm location decisions in Iowa and North Carolina, we find that measured agglomeration economies increase the probability of new firm entry in both urban and rural areas. Firms are more likely to locate in markets with an existing cluster of firms in the same industry, with greater concentrations of upstream suppliers or downstream customers, and with a larger proportion of college-educated workers in the local labor supply. Firms are less likely to enter markets with no incumbent firms in the sector or where production is concentrated in relatively few sectors. The same factors encourage both stand-alone start-ups and establishments built by multiplant firms. Commuting decisions exhibit the same pattern as new firm entry with workers commuting from low to high agglomeration markets. Because agglomeration economies are important for rural firm entry also, policies encouraging new firm entry should focus on relatively few job centers rather than encouraging new firm entry in every small town.
Keywords: dept.eco